Comparison of the effects of chronic desmethylimipramine administration on alpha 2- and beta-adrenoceptors in different regions of rat brain. - Stanford, C; Nutt, D; Cowen, P (1983)
The effects of ten once-daily injections of desmethylimipramine (10 mg/kg i.p.) on alpha 2- and beta-adrenoceptor binding were investigated in the rat cortex, hippocampus and hypothalamus. [3H]clonidine and [3H]dihydroalprenolol were used as ligands for alpha 2- and beta-adrenoceptors, respectively. Twenty-four hours after the last injection, the density of beta-adrenoceptors was reduced in all regions studied. In contrast, there was no change in alpha 2-adrenoceptor binding in the cortex, while increased binding was found in the hypothalamus. The effects of desmethylimipramine are discussed in relation to those of other antidepressant treatments.